STRATEGI POSITIONING DI PT.SHIROTOL JANNAH TOUR AND TRAVEL PEKANBARU - Melawati "; Musadad " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The backround of this research aims to knowing image. To identify the basic strategy and positionin process od PT shirotol jannah Tour and Travel in building the image. Positioning is interesting to study because it is one way to build the trust of consumers in building images. This research usesmethod qualitative method to process the data obtained in the field through interviews, observations and documentations. The analysis technique in the study uses a positioning strategy philip korter. Uses basic positioning strategies to find out how tu build an image wiht positioning strategi. The results of this study are PT. Shirotol jannah Tour and Travel applying corporate image that is service, product and price.using only 4 ( four ) basic strategy and using only 3 (three) positionin process. Keywords :Respon of visitors, resort and recepcionist